Study on the mechanics and self-sensing properties of ultrahigh-performance shotcrete containing waste glass aggregates - Jing Wang; Songze Wu; Yunlong Zhang; Xuesong Qian (Scientific Reports)
Abstract To promote the recycling of waste glass and satisfy the demands of environmental sustainability for ultrahigh performance concrete (UHPC), in this study, glass sand was employed to partially or entirely replace machine-made sand, and steel fibres were incorporated to fabricate ultrahigh performance shotcrete (UHPS). The effects of glass sand and steel fibres on the mechanical and electrical properties of composite materials were analysed in this study. Furthermore, alkali‒silica reaction (ASR) tests and microstructural analyses were conducted. The results indicate that at higher steel fibre contents, the incorporation of glass sand does not reduce the compressive strength of the UHPS and that glass sand has no significant effect on the split tensile or flexural strength. When the steel fibre content is 2% and the replacement ratio of glass sand reaches 100%, the mechanical properties of the UHPS reach their maximum. The addition of glass sand negatively affects the electrical properties, whereas the use of steel fibres improves them. The results of the alkali‒silica reaction tests confirm that the use of glass sand does not induce harmful expansion reactions. The study revealed the trends in the mechanical and electrical properties of concrete from a microstructural perspective and provided explanations for the alkali‒silica reaction outcomes. This study provides technical support for the application of UHPS to tunnel linings.